Single stage hydroprocessing of pyrolysis oil in a continuous packed‐bed reactor. Issue 3 (13th February 2014) - Parapati, Divya R.; Guda, Vamshi K.; Penmetsa, Venkata K.; Steele, Philip H.; Tanneru, Sathish K.
<x xml:space="preserve">Abstract</x> Raw bio‐oil cannot be combusted as transportation fuel directly because of its high acidity, high water content, lower heating value, and variable viscosity over time. Therefore, bio‐oil should be chemically converted to a more stable liquid product before subjecting it to hydrodeoxygenation (HDO) conditions. This research article focuses on catalytic hydroprocessing of pretreated bio‐oil (PTBO) in a single stage reaction using various catalyst compositions in a packed‐bed reactor. Four catalysts, a conventional hydrotreating catalyst (CoMo/γ‐Al2O3), an Fe‐Cr based mixed oxide catalyst, an FeW/Si‐Al catalyst, and a 1:2 mixture of Ru/γ‐Al2O3 and Ni/Si‐Al catalyst, were tested for conversion of the PTBO to mixed liquid hydrocarbons at 350–400°C, 1500 psig hydrogen pressure, and at a liquid hourly space velocity (LHSV) of 0.2–0.3 h−1. Liquid products produced from the HDO treatments were analyzed for properties such as acid value, heating value, elemental analysis, water content, and chemical characterization. The conventional hydrotreating catalyst, CoMo/γ‐Al2O3, performed the best among the four catalysts employed to reduced the acid value to 2 mg KOH/g and oxygen content to 0.1% while improving the heating value to 43 MJ/kg of the liquid product. The detailed hydrocarbon analysis of the reduced CoMo/γ‐Al2O3 upgraded hydrocarbon mixture showed the presence of olefins, iso‐paraffins, followed by naphthenes and aromatics. Simulated distillation results indicated that the liquid fuel had a boiling point range of 69–304°C, indicating the presence of petroleum equivalents of 50% gasoline (38–170°C), 30% jet fuel (170–250°C), and 20% diesel (250–304°C) range hydrocarbons. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 726–731, 2014